Outcomes of Patients Presenting With Clinical Indices of Spontaneous Reperfusion in ST‐Elevation Acute Coronary Syndrome Undergoing Deferred Angiography - Fefer, Paul (J Am Heart Assoc, 2017)
BACKGROUND: Few data are available regarding the optimal management of ST‐elevation myocardial infarction patients with clinically defined spontaneous reperfusion (SR). We report on the characteristics and outcomes of patients with SR in the primary percutaneous coronary intervention era, and assess whether immediate reperfusion can be deferred. METHODS AND RESULTS: Data were drawn from a prospective nationwide survey, ACSIS (Acute Coronary Syndrome Israeli Survey). Definition of SR was predefined as both (1) ≥70% reduction in ST‐segment elevation on consecutive ECGs and (2) ≥70% resolution of pain. Of 2361 consecutive ST‐elevation–acute coronary syndrome patients in Killip class 1, 405 (17%) were not treated with primary reperfusion therapy because of SR. Intervention in SR patients was performed a median of 26 hours after admission. These patients were compared with the 1956 ST‐elevation myocardial infarction patients who underwent primary reperfusion with a median door‐to‐balloon of 66 minutes (interquartile range 38–106). Baseline characteristics were similar except for slightly higher incidence of renal dysfunction and prior angina pectoris in SR patients. Time from symptom onset to medical contact was significantly greater in SR patients. Patients with SR had significantly less in‐hospital heart failure (4% versus 11%) and cardiogenic shock (0% versus 2%) (P<0.01 for all). No significant differences were found in in‐hospital mortality (1% versus 2%), 30‐day major cardiac events (4% versus 4%), and mortality at 30 days (1% versus 2%) and 1 year (4% versus 4%). CONCLUSIONS: Patients with clinically defined SR have a favorable prognosis. Deferring immediate intervention seems to be safe in patients with clinical indices of spontaneous reperfusion.